Corticotropin-releasing factor 1 receptor haplotype and cognitive features of major depression. Issue 1 (December 2018) - Davis, Elena; Keller, Jennifer; Hallmayer, Joachim; Pankow, Heather; Murphy, Greer; Gotlib, Ian; Schatzberg, Alan
Abstract Corticotropin-releasing factor signaling through CRF receptor type 1 (CRF1 ) has been shown to contribute to learning and memory function. A haplotype of alleles T-A-T in a set of common polymorphisms in the gene encoding for CRF1 (CRHR1 ) has been associated with both depression vulnerability and alterations in cognitive functioning. The present study investigated the relations between the TAT haplotype and specific symptoms of depression, self-reported ruminative behaviors, and neuropsychological performance on a learning and memory task. Participants were adults with major depression with and without psychotic features (N  = 406). Associations were examined between TAT haplotype and endorsement of depression symptoms from diagnostic interviews, scores on the rumination response scale (RRS), and verbal memory performance on the California Verbal Learning Test-II (CVLT-II). All analyses included depression subtype, age, and sex as covariates; CVLT-II analyses also included evening cortisol levels. Across the entire sample, carriers of more copies of the TAT haplotype reported greater endorsement of the symptom describing difficulty concentrating and making decisions. In separate subsamples, TAT homozygotes had higher rumination scores on the RRS, both brooding and reflection subscales, and more TAT copies were associated with poorer CVLT-II performance in both total learning and free recall trials. These data demonstrate that theCRHR1 TAT haplotype is associated with cognitive features of depression including difficulty with decision-making, higher rumination, and poorer learning and memory. It will be important in future research to identify the specific molecular mechanisms for CRF1 signaling that contribute to depression-related cognitive dysfunction.